The Expression of CD28 and Its Synergism on the Immune Response of Flounder (Paralichthys olivaceus) to Thymus-Dependent Antigen - Xing, Jing; Liu, Wenjing; Tang, Xiaoqian; Sheng, Xiuzhen; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2021)
CD28 is well known as a critical T-cell costimulatory receptor involved in T cell activation by binding to its ligands. In this study, CD28 was cloned, and its expression profiles were characterized in flounder (Paralichthys olivaceus); variations of CD28+ cells after being stimulated with different types of antigens and the function of the CD28 costimulatory pathway on T-cell activation were investigated in vitro. fCD28 consists of four exons and three introns, and the full-length cDNA of fCD28 was 675-bp encoded 224 amino acids. The conserved motif (121TFPPPF126) binding to the CD80/86 ligand exists in the Ig-superfamily homology domain. The high expression of fCD28 is in gills, PBLs, head kidney, and spleen. CD28+ cells were co-localized with CD4+ T lymphocytes but not on IgM+ B lymphocyte cells. Moreover, the expression of CD28 was significantly varied in flounder after being stimulated by keyhole limpet hemocyanin (KLH) at both the transcriptional and cellular levels, while no significant differences were observed between lipopolysaccharide (LPS) stimulation and the control group. Notably, treatment of PBLs cultured in vitro with CD28 molecule-specific antibody (anti-CD28 Abs) and PHA produced more cell colonies and stimulated the proliferation of cultured leukocytes compared to PHA stimulation alone and the control group, and a higher level of IL-2 was detected in the culture medium. Meanwhile, anti-CD28 Abs increased the percent of CD28+ cells (10.41 ± 1.35%), CD4+ T lymphocytes (18.32 ± 2.15%), and CD28+/CD4+ double-positive cells (6.24 ± 1.52%). This effect also resulted in significant variations in the genes of cell membrane-bound molecules, cytokines, and related signaling pathways in cultured leukocytes, with significant changes in the genes of interleukin-2 (IL-2) and nuclear factor of activated T cells (NFAT) in the early stages of culture, and the expression of other molecules increased over time. These results proved the localization of the CD28 molecule on T lymphocytes in flounder, and anti-CD28 may act as the B7 ligand involved in T cell activation after antigen stimulation. These data provide a basis for a more in-depth study of the mechanism of the CD28 costimulatory pathway in T cell activation.